Role Play Game (RPG) to Improve Student Problem Solving Skills - Retno Andriyani; Nisvu Nanda Saputra; Abdul Baist (RANGE: Jurnal Pendidikan Matematika, 2024)
This research is to develop Role Play Game (RPG) learning media to improve students' problem-solving skills. The type of research used is development research with the ADDIE development model (Analysis, design, Development, Implementation, Evaluation), with the subject of research being grade VIII students of SMP Dharma Siswa Kota Tangerang with a total of 33 subjects. Data collection techniques use validation sheets, student response questionnaires, and problem-solving test instruments. From the results of the study, it is known that RPG learning media is feasible to use based on the results of validator assessments and student responses after using learning media, then RPG learning media can be used in learning to improve students' problem-solving abilities, students' problem-solving abilities increased from 33.30% to 75.75%. So it can be concluded that RPG learning media is suitable for use in the classroom and can improve students' problem-solving skills